Penerapan Metode Resource Loaded Scheduling Untuk Aplikasi Manajemen Proyek Pada Perusahaan Kontraktor “X” - David Filigon Lie; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2021)
Currently PT. Liberty Persada Sakti still uses CPM method when making schedule, because CPM does not factor in resources the result is not that accurate for estimating time period of a project. And all records of transactions done and calculation of RAB still done manually in papers and microsoft excel, that causes the company became susceptible for mistake made in calculating finance.Looking at the background of the problem, an appliaction is designed to help PT. Liberty Persada Sakti. The application will use Resouce Loaded Scheduling method for making schedule for a project, recording company finance and controlling project management. Application will uses PHP programming language and MySQL for making database.The results obtained from this thesis is that, the new system is helping the company to create and record RAB, and by comparing the calculated result from CPM and Resource Loaded Scheduling, both method have it’s own advantages and disadvantages.